2010
DOI: 10.1051/0004-6361/200913359
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the Galactic center region in HCO+, H13CO+, and SiO

Abstract: Aims. A large-scale survey of the Galactic center region in the 3 mm rotational transitions of SiO, HCO + and H 13 CO + (beamsize ∼3. 6) was conducted to provide an estimate of cloud conditions, heating mechanisms, chemistry, and other properties. Methods. Using the NANTEN 4 m telescope from Nagoya University, a region between −5. • 75 < l < 5.• 6 and −0.• 68 < b < 1.• 3 was mapped in the J = 1 → 0 lines of HCO + and H 13 CO + and in the J = 2 → 1 line of SiO with a spacing of 3. 75 (HCO + ) and 1. 875 (SiO an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 54 publications
(103 reference statements)
5
53
0
Order By: Relevance
“…It has been observed previously by several authors (Bitran et al 1997;Fukui et al 2006;Sawada et al 2001;Lee & Lee 2003;Riquelme et al 2010b); its main velocity component is at 98 km s −1 (from the HCO + data from Riquelme et al 2010b), and a large velocity width in all the species is observed in this and previous works, which indicates that this source indeed belongs to the GC region. …”
Section: Single Temperature Regime In the Loop Regionsupporting
confidence: 83%
See 2 more Smart Citations
“…It has been observed previously by several authors (Bitran et al 1997;Fukui et al 2006;Sawada et al 2001;Lee & Lee 2003;Riquelme et al 2010b); its main velocity component is at 98 km s −1 (from the HCO + data from Riquelme et al 2010b), and a large velocity width in all the species is observed in this and previous works, which indicates that this source indeed belongs to the GC region. …”
Section: Single Temperature Regime In the Loop Regionsupporting
confidence: 83%
“…The beam width of the telescope at 23.7 GHz is 42.2 . The spectra were observed in position-switching mode, with the emission-free reference positions from Riquelme et al (2010b), which were checked in the first setup, where the most intense lines are detected. Each position was observed for 12 min in the first setup, 24 min in the second setup, and 32 min in the third setup.…”
Section: Effelsberg Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Fukui et al (2006) discovered two large molecular loops, loop 1 and loop 2, at a radius of 700-pc from the center, which are triggered by magnetic buoyancy (Parker instability;Parker 1966); while the main focus in Parker (1966) was aimed at the Galactic disk, he already suggested that the magnetic activity might become even more important in the central few 100 pc. Subsequently, Fujishita et al (2009);Torii et al (2010a,b); Riquelme et al (2010); Kudo et al (2011) presented analyses of more detailed observational properties of these molecular loops, and it was shown that the molecular loops are also well reproduced by magneto-hydrodynamical (MHD, hereafter) simulations (Shibata & Matsumoto 1991;Machida et al 2009;Takahashi et al 2009). …”
Section: E-mail: Stakeru@nagoya-ujp (Tks)mentioning
confidence: 99%
“…Three of them are located at the foot points and two at the top of the loops. Two positions are in the disk toward the locations of the expected interactions between the X1 and X2 orbits (Disks X1 and X2 in Tables 2, 3 The positions at the foot points of the GMLs were selected from the intensity peaks of the SiO maps of Riquelme et al (2010) and from previous results from higher angular resolution mapping with the Mopra-22 m telescope (Riquelme et al, in prep.). The Fukui et al (2006) maps of the GMLs were used to select the position at the top of the loop.…”
Section: Observationsmentioning
confidence: 99%